Efficacy of multimedia teaching on learning and retention of arithmetic in autistic students - Daryosh Norozi; Ahmad Ahmad zade bayani; Najmi Agha barati (Ravānshināsī-i Afrād-i Istis̠nāyī, 2012)
Objective: The purpose of this research is to assess the effect of traditional teaching and multimedia on the learning and retention of mathematics in autistic students of the fifth grade of elementary school in the city of Tehran. Method: In this research, 8 autistic boy students of the fifth grade of elementary school were selected and assigned randomly into control and experimental groups, 4 students in each group. To start a test of homogeneity between the groups was made. After assuring the homogeneity of the two groups the experimental group was taught via a researcher made multimedia package while the control group undergoes the traditional and teaching. The time plan for each instruction method for each group has been 4 sessions. In each group four learning and retention posttests of the content about diamond and trapezoid were conducted. Results: Data analysis via using t-test showed that applying the multimedia is more effective than the traditional teaching of mathematics concerning autistic students .In other words the results indicated that teaching via multimedia has a meaningful effect on the learning and retention of the autistic student. Conclusion and recommendations: Vaster application and use can be made of the multimedia modus of teaching autistic students.